2015
DOI: 10.1007/s00391-015-0904-1
|View full text |Cite
|
Sign up to set email alerts
|

„Aging Brain Care Program“ aus Indianapolis

Abstract: From the perspective of the authors the core elements of the program include not only the use of a home-based care model but also the selection and training of a new type of front-line care provider. Models like the program presented here show great promise for meeting the demands of a rapidly expanding population of vulnerable older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Thus, our results indicate meaningful clinical relevance. The study methods were in line with the demand to use standardized sets of outcome measures and well-defined interventions to improve comparability across studies, and our results contribute empirical evidence to currently inconclusive research on DCM approaches in primary care.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, our results indicate meaningful clinical relevance. The study methods were in line with the demand to use standardized sets of outcome measures and well-defined interventions to improve comparability across studies, and our results contribute empirical evidence to currently inconclusive research on DCM approaches in primary care.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the review concluded that studies that are rigorous in design and intervention delivery are needed . Intervention modules and a standard set of outcome measures should furthermore be clearly defined to improve comparability …”
Section: Introductionmentioning
confidence: 99%
“…The number of people with dementia is projected to triple by 2050. In the United States, it is estimated that Alzheimer's disease and other forms of dementia will cost over $290 billion in 2018 (Ghoge et al, 2003;Robertson et al, 2016;Villarreal et al, 2016;Vollmar et al, 2016). In addition to the direct costs of care, there is a significant indirect cost associated with dementia, such as loss of productivity, informal care, and reduced quality of life for people with dementia and their caregivers (Gallagher et al, 2009;Pathak & Biswal, 2021;Perkins et al, 2022).…”
mentioning
confidence: 99%